Use of nouns and verbs in the oral narrative of individuals with hearing impairment and normal hearing between 5 and 11 years of age - Amemiya, Érica Endo; Goulart, Bárbara Niegia Garcia; Chiari, Brasilia Maria (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Nouns and verbs indicate actions in oral communication. However, hearing impairment can compromise the acquisition of oral language to such an extent that appropriate use of these can be challenging. The objective of this study was to compare the use of nouns and verbs in the oral narrative of hearing-impaired and hearing children. DESIGN AND SETTING: Analytical cross-sectional study at the Department of Speech-Language and Hearing Sciences, Universidade Federal de São Paulo. METHODS: Twenty-one children with moderate to profound bilateral neurosensory hearing impairment and twenty-one with normal hearing (controls) were matched according to sex, school year and school type. A board showing pictures was presented to each child, to elicit a narrative and measure their performance in producing nouns and verbs. RESULTS: Twenty-two (52.4%) of the subjects were males. The mean age was 8 years (standard deviation, SD = 1.5). Comparing averages between the groups of boys and girls, we did not find any significant difference in their use of nouns, but among verbs, there was a significant difference regarding use of the imperative (P = 0.041): more frequent among boys (mean = 2.91). There was no significant difference in the use of nouns and verbs between deaf children and hearers, in relation to school type. Regarding use of the indicative, there was a nearly significant trend (P = 0.058). CONCLUSION: Among oralized hearing-impaired children who underwent speech therapy, their performance regarding verbs and noun use was similar to that of their hearing counterparts.